Reframing islamic educational management: A maqasid-driven governance model for 21st-century learning institutions - Hamdanah (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
This study re-examines the foundations of Islamic educational management by proposing a governance model grounded in the Maqasid al-Shari‘ah and oriented towards the demands of twenty-first-century learning. While contemporary institutions face mounting pressures related to digitalisation, inclusivity, and accountability, many governance frameworks remain fragmented, technocratic, or disconnected from the holistic philosophy of Islamic education. This research adopts a qualitative design, integrating textual analysis of classical sources with thematic exploration of modern governance literature. The resulting framework identifies two core domains: the normative–ethical grounding and the structural–operational mechanisms of governance. The normative domain includes intentionality (niyyah), preservation of human dignity, and the cultivation of virtue as institutional ethos. The structural domain encompasses epistemic design, policy coherence, learner-centred systems, and adaptive leadership capable of responding to rapid socio-technological change. Findings reveal that a Maqasid-driven governance model offers a comprehensive scaffold for institutional transformation by linking ethical commitments with managerial functionality. Rather than treating Maqasid as merely theological ideals, the model reconceptualises them as strategic levers that can guide curriculum design, organisational culture, staff development, and accountability practices. The study argues that adopting this approach enhances institutional resilience, strengthens value-integration, and improves educational relevance in Muslim contexts navigating global shifts. This research contributes a theoretically grounded and operationally viable governance blueprint for Islamic educational institutions seeking to bridge classical wisdom with contemporary educational imperatives